Sul crepuscolo e sull’aurora come immagine dialettica fra razionalità e rêverie in Bachelard - Castelli Gattinara, Enrico (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
To understand all the nuances and originality of bachelardian philosophy, it is necessary to pay attention to the “auroral” and “crepuscular” aspects of his thought. Some theoretical, rational and imaginary spaces are intermediate between those of the day (epistemological rationality) and those of the night (the dreamlike and libidinal imaginary). Only by considering be important these spaces of uncertainty, in a certain sense “impure” and approximated, we can grasp the force that allows scientific knowledge to evolve and transform itself thanks to the energies hidden in the poetic imagination. At the same time, however, we can learn that poetry, without knowledge, would be just a nocturnal nightmare unable to give us that happiness and rest that the French philosopher so much sought. In this text we will try to show how much importance Bachelard gave, in his writings, to these intermediate spaces, despite the clear separation that he has always reiterated between rational reason and imagination.